Perceptions Towards E-Book Usage in Universities A Case Study: Ajman University - Shishakly, Rima; Gheyathaldin, Lilian (International Journal of Engineering and Technology, 2019)
Electronic Books (E-books) have received swift acceptance amongst higher education institutions around the world. Universities, as well Ajman University (AU) in the United Arab Emirates, have been using technology effectively in teaching methods and learning processes. Since 2013, Ajman University provided e-books to the students in different colleges.The purpose of this study is to understand the studentsâ€™ sentiments between the uses of textbook, compared to e-books. The study discusses different factors that affect the acceptance or the resistance of students toward using e-books as part of their course materials.The study emphasized studentsâ€™ negative attitude towards e-book usage. Of those who did prefer e-book usage, low cost was number one reason. Furthermore, it discusses the different factors that resulted in studentsâ€™ attitudes towards e-book use as part of their course materials. The study showed that both the need to learn and technical skills, similarly affect their negative perceptions and reflect the loyalty of students to printed textbooks.Â